Nanolayered Topsheet Integration for Enhanced Antimicrobial Properties in Sanitary Napkins - A., Harini; K., Seethalakshmi; Deepika, Balasubramanian; Thirumalai, Anbazhagan; P.S., Sharon Sofini; Perumal, Ilaiyaraja; Girigoswami, Agnishwar; Girigoswami, Koyeli (Current Molecular Medicine, 2026)
<span class=
Keywords: top sheet